Dehydroleucodine inhibits mitotic clonal expansion during adipogenesis through cell cycle arrest - Abood, S. (2018)
Aberrant levels of preadipocyte differentiation, triggered by adipocyte hyperplasia and hypertrophy, results in the obesogenic phenotype. Obesity is a risk factor for several metabolic disorders. In this paper, dehydroleucodine inhibited the accumulation of lipid droplets and decreased the elevations of triglycerides, and this inhibitory effect occurred during the early stage of adipogenesis. Thus, not only did dehydroleucodine downregulate the expression of C/EBPα and PPARγ, it also strongly blocked the expression of C/EBPβ, an early stage biomarker of early adipogenesis, in a concentration-dependent manner. The proliferation of preadipocytes was dramatically suppressed when dehydroleucodine was added to the medium as early as 24 hr. These results indicate that dehydroleucodine may specifically affect mitotic clonal expansion to inhibit preadipocyte differentiation. Dehydroleucodine arrested the cell cycle at the G0/G1 phase, increased p27 and decreased both cyclins A and D and their partners (e.g., CDK2 and CDK4). Additionally, dehydroleucodine decreased phosphorylation of Erk1/2 and Akt. Furthermore, dehydroleucodine downregulated expression of histone demethylase JMJD2B as well as repressed the expression of histone methyltransferase MLL4, which in turn diminished the expression of C/EBPβ and PPARγ, respectively. Collectively, our results indicate that dehydroleucodine inhibits preadipocyte differentiation by blocking mitotic clonal expansion via cell cycle arrest, which may be mediated by regulation of selective histone methylation/demethylation in transcription activation during the early step of adipogenesis.